Metal and metalloid determination in biodiesel and bioethanol. Issue 1 (9th October 2014) - Sánchez, Raquel; Sánchez, Carlos; Lienemann, Charles-Philippe; Todolí, José-Luis
Abstract : Biofuel quality control involves the determination of metal and metalloid content. Abstract : Biofuel quality control involves the determination of metal and metalloid content. These species play a very important role because they may modify the efficiency of biofuel production as well as the stability of these products. Furthermore, some metals are toxic and generate environmental concerns whereas others are used as additives. Normally, products such as biodiesel and bioethanol are mixed with conventional fossil fuels (diesel and gasoline, respectively). Therefore, metals come from the raw product employed for biofuel production (seeds, sugars…) as well as from the production and storage process or even from the added fuels. The determination of the final metal and metalloid concentration in biofuels is a challenging subject because of several reasons. On the one hand, their content is usually low ( i.e., from several μg L −1 to mg L −1 ) and, hence, sensitive techniques should be used. Besides all these, calibration with organic complex matrices becomes more difficult and degrades the accuracy of the determination. Several approaches have been evaluated to carry out this kind of analysis going from spectrochemical to electroanalytical techniques. Within the first group, Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) and Mass Spectrometry (ICP-MS) are often employed together with atomic absorption methods. The different procedures applied will be discussed in the present review emphasizing the most widely employed ones. On this subject, fundamental as well as applied studies related to the biofuel analysis through ICP-OES and ICP-MS will be shown to illustrate the current difficulties associated with these determinations. Comments regarding the possible solutions proposed to overcome the drawbacks encountered will be made.